Tingkat Pengembalian Modal dalam DuPont System Model - Teguh, Doni; Yulaiha Fitriah (Jurnal Bisnis Islam dan Kewirausahaan, 2024)
This study is to analyze the rate of return on capital in the DuPont Model System, in the Industrial Sector Companies of the Indonesia Stock Exchange. The method used in this study is a descriptive quantitative method which explanatory research, about the causal correlation relationship to determine the relationship between net profit margin, total asset turnover, and financial leverage to the rate of return on equity measured through Return on Equity, with a sampling of the population of the top ten constituents industrials. The results of the study, showing the rate of Return on Euqity, using the equation allow companies to see more clearly what drives the rate of return on equity and what is the relationship between net profit margin, asset turnover and debt ratio. Seven companies; ARNA, HEXA, IMPC, BNBR, ABMM, BHIT, BMTR ensure that the business that is being run is able to run well and get the expected profits. Three companies were able to record a return on capital based on the DuPont formula; ARNA, HEXA, and IMPC. The three companies were able to generate a return on equity from optimizing asset turnover, net profit, and equity indicators. The DuPont model concludes that companies can increase their return on equity by maintaining high profit margins, improving asset turnover, and utilizing their assets more effectively. The DuPont model approach gives the company's management two options; First, by increasing the overall asset turnover ratio through sales and operating income, which ultimately has an impact on the company's net profit level. Second, by increasing the company's assets through capital, both its own capital and capital obtained from debt